P066 COVID Voices: co-produced research to explore the shielding experiences of people with inflammatory musculoskeletal disease. (23rd April 2022) - Fox, Joyce; Laidlaw, Lynn; Dixon, William G; Sanders, Caroline; Sharp, Charlotte A
Abstract: Background/Aims: Up to one-third of people living with inflammatory arthritis or auto-immune disease may have been classified as 'clinically extremely vulnerable' (CEV) to COVID-19 and required to 'shield'. Communication regarding shielding notification and details of how to shield were unclear, causing confusion and uncertainty. Most research into the impact of shielding on people living with musculoskeletal disease has involved either quantitative or survey-based data, with little patient involvement. This project aims to capture patient "stories" to understand and explore the experiences of people with inflammatory musculoskeletal conditions who shielded, using co-produced, qualitative methodology. Methods: The Centre for Epidemiology Versus Arthritis (CfE) is committed to involving patients and the public, convening a COVID-19 Patient and Public Involvement (PPI) group early in the pandemic. Two PPI group members developed the research idea and collaborated with a clinical academic to co-produce a successful grant application to the Versus Arthritis "New opportunities" fund. The research aims to capture experiences and opinions on the processes for determining and communicating who is identified as CEV, and the impact of shielding upon individuals' lives. We will develop recommendations to improve the process for subsequent pandemics. People who shielded due to inflammatory arthritis / auto-immune disease are invited to discuss their experiences of shielding in semi-structured interviews (n = 30) or focus groups (n = 12). Up to 50 participants may submit creative materials (artwork, poetry, photographs or written word), to include those unable, or unwilling, to speak about their experiences. A framework approach to thematic analysis of data generated from interviews and focus groups will be employed. Creative materials will be used to illustrate these themes. In addition to the core team, an experienced Patient Advisory Group will contribute to the analysis. Full ethical approval was awarded by the University of Manchester Research Ethics Committee. The 'core team' (two patient/public contributors and a clinical academic) are committed to 'co-production': working together in equal partnership, driven by values such as transparency, sharing power and inclusivity, which we anticipate will improve the relevance and quality of this work. Results: Recruitment to interview and focus groups was exceeded within 10 days. Half the creative materials participants were recruited within a month, and recruitment remains open. The team have given invited talks at several national and regional events, discussing the research and methodological approach, demonstrating the significant interest generated by this work. Conclusion: Although most funders now mandate some form of PPI in grant applications, research ideas conceived and genuinely co-produced by patient partners are rare. The CfE's commitment to PPI enabled conversations and collaboration, which built on existing relationships, and led to successful grant funding. We look forward to further highlighting and sharing both the model of our collaboration, and the qualitative research findings. Disclosure: J. Fox: None. L. Laidlaw: None. W.G. Dixon: Consultancies; WGD has received consultancy fees from Abbvie and Google, unrelated to this work. C. Sanders: None. C.A. Sharp: None.